Modes of effective physical education of students in the conditions of modern education - Исмаилова, Светлана; Мукушева, Алма (Pedagogy and Psychology, 2021)
The article is devoted to the main directions of increasing the effectiveness of physical education of students. Attention is paid to the phenomenon of efficiency in the context of teaching physical culture in a higher educational institution. The social, organizational, managerial, psychological prerequisites for effective management of physical education are indicated. The techniques, methods and means that influence the effectiveness of physical culture and sports lessons are described. The authors refer to the main directions of increasing the effectiveness of physical education as improving the material and technical support of the educational process, holding sports competitions, organizing an integrated physical culture and sports environment, motivating regulation, maximizing the developmental load, organizing independent studies, using non-traditional types of physical exercises, introducing innovative technologies. The article provides examples of pedagogical research for each of these areas. The analysis of scientific publications is based on the work of scientists from neighboring countries.